Legal Protection for Depositor Customers in Digital Banks Against Cyber Crimes in the Banking Sector - Br. Tarigan, Agita Justisia; Rwa Jayantiari, I Gusti Agung Mas (Westscience Press, 2025)
The full use of technology in running a digital bank makes things easier for customers but is vulnerable to cybercrime in the banking sector which can harm customers. This research places the main focus on forms of legal protection efforts for customers who deposit at digital banks against the occurrence of cybercrime in the banking sector. Legal problems, namely regarding the legal relationship between deposit customers and digital banks in banking sector cyber crime issues as well as legal protection efforts for deposit customers in digital banks in banking sector cyber crime issues. The type of research applied is normative legal research using statutory, conceptual and analytical approaches to examine the problems discussed. The research results show that the legal relationship between digital banks and customers who deposit funds is a relationship of trust (fiduciary relationship) contained in the funds deposit agreement. Legal protection for deposit customers in cases of cyber crime includes: 1) Preventive legal protection in the form of preventing losses for deposit customers in accordance with the provisions of the Banking Law, POJK Number 12/POJK.03/2018, as well as related legal instruments; and 2) Repressive legal protection in the form of dispute resolution efforts which can be implemented in 2 (two) ways, namely Non-Litigation and Litigation dispute resolution. Efforts to resolve non-litigation disputes, namely: 1) Making a complaint to PUJK; 2) Make a complaint to the OJK. Meanwhile, the litigation effort is to file a civil lawsuit.